A Flexible, Low-Cost Hydroponic Co-Cultivation System for Studying Arbuscular Mycorrhiza Symbiosis - Das, Debatosh; Torabi, Salar; Chapman, Philipp; Gutjahr, Caroline (Frontiers in Plant Science, 2020)
Arbuscular mycorrhiza (AM) is a widespread symbiosis between plant roots and fungi of the glomeromycotina, which improves nutrient uptake by plants. The molecular mechanisms underlying development and function of the symbiosis are subject to increasing research activity. Since AM occurs in the soil, most studies targeting a molecular understanding of AM development and function, use solid substrates for co-cultivating plants and AM fungi. However, for some experiments very clean roots, highly controlled nutrient conditions or applications of defined concentrations of signalling molecules (such as hormones) or other small chemicals (such as synthetic inhibitors or signaling agonists) are needed. To this end, hydroponics has been widely used in research on mechanisms of plant nutrition and some hydroponic systems were developed for AM fungal spore amplification. Here, we present a hydroponics set-up, which can be successfully utilized for experimental root colonization assays. We established a “tip-wick” system based on pipette tips and rock wool wicks for co-cultivation of AM fungi with small model plants such as Lotus japonicus. A larger “falcon-wick” system using Falcon tubes and rockwool wicks was developed for larger model plants such as rice. The hydroponic system can also be employed for growing Lotus japonicus hairy roots after transformation by Agrobacterium rhizogenes, thus circumventing the laborious cultivation on agar medium-containing Petri dishes during hairy root development. The tip-wick and falcon-wick systems are easy to use and can be built with low cost, conventional and reusable lab plastic ware and a simple aquarium pump.